2018
DOI: 10.5194/acp-2017-1115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal influences on surface ozone variability in continental South Africa and implications for air quality

Abstract: Although elevated ozone (O3) concentrations are observed in many areas within continental southern Africa, few studies have investigated the regional atmospheric chemistry and dominant atmospheric processes driving surface O3 formation in this region. The aim of this study was to 20 conduct an assessment of comprehensive continuous surface O3 measurements performed at four sites located in continental South Africa. These sites were representative of regional background (Welgegund and Botsalano) and industrial … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 41 publications
(82 reference statements)
2
26
0
Order By: Relevance
“…In Kenya and other countries of Africa, coal and petroleum consumption are also increasing rapidly, due in part to increased vehicle use, and ozone precursor emissions are anticipated to increase further due to NO release from soils as additional N is added to increase crop yield (Hickman et al, ). Northern and Southern Africa have been identified as among the regions most at risk from very high ozone concentrations under a “policy fail” SRES A2‐type emissions scenario (Laban et al, ; Royal Society, ) unless measures are taken to reduce precursor emissions (Wild et al, ). One of the sources of precursors is biomass burning, and regions of tropical biomass burning have elevated ozone compared to the rest of the tropics (Anderson et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Kenya and other countries of Africa, coal and petroleum consumption are also increasing rapidly, due in part to increased vehicle use, and ozone precursor emissions are anticipated to increase further due to NO release from soils as additional N is added to increase crop yield (Hickman et al, ). Northern and Southern Africa have been identified as among the regions most at risk from very high ozone concentrations under a “policy fail” SRES A2‐type emissions scenario (Laban et al, ; Royal Society, ) unless measures are taken to reduce precursor emissions (Wild et al, ). One of the sources of precursors is biomass burning, and regions of tropical biomass burning have elevated ozone compared to the rest of the tropics (Anderson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although other air pollutants are also present in tropical regions, including fine particles PM 2.5 (Brauer et al, ), ozone concentrations are increasing rapidly and there is less potential to control concentrations locally than for some other pollutants such as PM 2.5 due to the hemispherical transport of ozone precursors. Although there is some sporadic monitoring of air pollutants including ozone in some parts of Africa, particularly in south Africa (Laban et al, ), there is currently very little monitoring of ambient ozone concentrations across most of Africa (Schultz et al, ) and where data are available time series are often short. Reported values often tend to be as 24 hr mean values, which may not be representative of daytime mean concentrations when plants are active, and these daytime concentrations would be expected to be much higher than those during the night due to the diurnal profile of ozone concentrations observed in urban areas, for example Hanoi (Sakamoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The north-eastern interior of South Africa, where these sites are located, is generally characterised by increased concentrations in pollutant species during the dry winter months (June to September) due to the prevailing meteorological conditions (Conradie et al, 2016). More pronounced inversion layers trap pollutants near the surface, which, in conjunction with increased anticyclonic recirculation and decreased wet deposition, leads to the build-up pollutant levels (Conradie et al, 2016;Laban et al, 2018 observed periods of decreased and increased SO2 and NO2 levels are also indicated by the three-year moving averages of the annual mean SO2 and NO2 concentrations at all three sites.…”
Section: Seasonal and Inter-annual Variabilitymentioning
confidence: 96%
“…Moreover, a large number of these sources are located within the north-eastern interior of South Africa, and include the Mpumalanga Highveld, the Johannesburg-Pretoria conurbation and the Vaal Triangle. Laban et al (2018), for instance, recently indicated high O3 levels in this northeastern interior of South Africa, while it was also indicated that O3 formation in this region can be considered NOx-limited due to high NO2 concentrations. Therefore, the South African A number of studies have been reported on measurements conducted within the INDAAF network (Martins et al, 2007;Adon et al, 2010;Josipovic et al, 2011;Adon et al, 2013), https://doi.org/10.5194/acp-2020-166 Preprint.…”
Section: Introductionmentioning
confidence: 99%